Species of the genus Munidopsis (Crustacea, Decapoda, Gala-theidae) from the deep Atlantic Ocean, including cold-seep and hydrothermal vent areas - Macpherson, Enrique; Segonzac, Michel (Zootaxa, 2005)
Twenty-two species of the genus Munidopsis from the Atlantic Ocean are studied. Five new species are described (M. anemia, M. exuta, M. hirtella, M. laurentae and M. truculenta), and diagnoses and illustrations of some relatively rare species (M. acuminata, M. bairdii, M. livida, M. parfaiti and M. thieli) are provided. None of the species discussed here is restricted to a particular habitat, including species collected from hydrothermal vent (M. acutispina, M. exuta) and cold seep areas (M. acutispina, M. geyeri, M. hirtella, M. livida, M. marionis). The new records of some species greatly extend the previously known distribution range of the species (i.e., M. abyssicola, M. aries, M. bairdii, M. geyeri, M. livida, M. parfaiti, M. thieli). Finally, some biological and biogeographical data for the different species are discussed.